Dual-step photocarrier injection by mixture layer of ZnO QDs and MoS2 NPs on hybrid PdAu NPs. (July 2022) - Mandavkar, Rutuja; Lin, Shusen; Kulkarni, Rakesh; Burse, Shalmali; Habib, Md Ahasan; Kunwar, Sundar; Lee, Jihoon
Abstract: Hybrid UV-photodetector (PD) design consisted of various compatible nano-material systems are drawing significant research interests due to their improved device tunability and functionality. A hybrid ZnO–MoS2 /HNP UV-PD design is demonstrated by the mixture layer of zinc oxide (ZnO) quantum dot (QD) and molybdenum di-sulfate (MoS2 ) nanoparticles (NPs) on the plasmonic hybrid PdAu NP template. The proposed design exhibits an excellent photocurrent of 1.45×10 −3 A under the 54.9 mW/mm 2 at ± 10 V due to a dual step enhancement of photo-carrier injection. It then leads to the significantly improved performance factors of photo-responsivity 1430 mA/mm 2 and detectivity 4.50 × 10 10 jones at 0.34 mW/mm 2 . The rise time ( Tr ) and fall time ( Tf ) of 3.37 and 0.35 s are obtained for the ZnO–MoS2 /HNP PD. The demonstrated performance factors indicate that the hybrid ZnO–MoS2 /HNP UV-PD platform is one of the best UV-PDs as summarized in Table 1. Highlights: Demonstration of a novel hybrid photodetector architecture of MoS2 –ZnO on hybrid PDAu NPs. Superior device performances: photoresponsivity of 1430 mA/W, detectivity of 4.50 × 1010 jones and EQE of 460%. Systematic comparison of photoresponse of bare ZnO, ZnO/HNPs and MoS2 –ZnO/HNP UV-PD. Detailed explanation for photocurrent enhancement mechanism by the FDTD simulation, cross-sectional analyses, and energy band diagram. A hybrid UV photodetector design is demonstrated by the mixture layer of zinc oxide (ZnO) quantum dot (QD) and molybdenum di-sulfate (MoS2 ) nanoparticles (NPs) on the plasmonic hybrid PDAu NP template, namely, hybrid ZnO–MoS2 /HNP UV photodetector. Graphical abstract: Image, graphical abstract